Development of an Advance Warning Indicator of External Debt Servicing Vulnerability - Abdullah, Fuad A. (Journal of International Business Studies, 1985)
The main objective of this paper is to develop a leading indicator of external debt servicing vulnerability that would serve as an advance signal of payments interruption. The traditional and widely used ratios of debt servicing capacity, such as the ratio of the balance on current account of debt service payment, and the ratio of external debt to exports among others, primarily measure a country’s current capacity to handle its international obligations. However, they fail to test the vulnerability to debtor countries to oncoming debt servicing problems, or to signal in advance an imminent situation of payments interruption.